Integrating Advanced Wastewater Treatment and Molecular Tools for Sustainable Water Quality Management in Intensive Aquaculture Systems - Nur Aifiah Binti Ibrahim Ibrahim (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2026)
Aquaculture is a rapidly growing food production sector that supports global food security and livelihoods, but generates nutrient-rich wastewater and relies on chemical treatments that can harm aquatic ecosystems. Conventional water management strategies, such as sedimentation and biofiltration, are often insufficient to address challenges associated with organic loading, nutrient accumulation, and disease outbreaks in intensive and recirculating systems. Advances in molecular tools, including genomics and transcriptomics, enable better monitoring of fish health and environmental stress responses, while emerging treatment technologies, such as microbial bioremediation and membrane filtration, offer potential for nutrient recovery and pollution reduction. Despite these innovations, integration of molecular insights with sustainable water management remains limited. This study aims to develop an integrated approach for improving aquaculture water quality, combining advanced wastewater treatment technologies with molecular tools to enhance environmental sustainability, fish health, and productivity. The findings provide a framework for safer, more efficient, and environmentally responsible aquaculture practices, addressing both ecological and operational challenges in modern intensive systems.